2000
DOI: 10.1128/jvi.74.9.4335-4350.2000
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Amino Acid Variability of the Human Immunodeficiency Virus Type 1 gp120 Envelope Glycoprotein and Prediction of New Discontinuous Epitopes

Abstract: To elucidate the evolutionary mechanisms of the human immunodeficiency virus type 1 gp120 envelope glycoprotein at the single-site level, the degree of amino acid variation and the numbers of synonymous and nonsynonymous substitutions were examined in 186 nucleotide sequences for gp120 (subtype B). Analyses of amino acid variabilities showed that the level of variability was very different from site to site in both conserved (C1 to C5) and variable (V1 to V5) regions previously assigned. To examine the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
45
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 68 publications
9
45
1
Order By: Relevance
“…This lack of lineage-specific model significance is most likely due to the much shorter sequence data used (150 codons) and the fact that the fragments covered the V3-V5 region, where only 20% of category II sites were observed in the full gene. A strong correlation was observed between sites identified as category II amino acids in this study and sites observed as undergoing strong evolutionary constraints in other studies (4,(27)(28)(29). For example, 50% of the subtype K category II sites in the gp120 three-dimensional structure were determined to be undergoing strong selective pressures in at least one of the other studies examined (4,(27)(28)(29) (Table 2).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This lack of lineage-specific model significance is most likely due to the much shorter sequence data used (150 codons) and the fact that the fragments covered the V3-V5 region, where only 20% of category II sites were observed in the full gene. A strong correlation was observed between sites identified as category II amino acids in this study and sites observed as undergoing strong evolutionary constraints in other studies (4,(27)(28)(29). For example, 50% of the subtype K category II sites in the gp120 three-dimensional structure were determined to be undergoing strong selective pressures in at least one of the other studies examined (4,(27)(28)(29) (Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…There was little correlation between category I sites and amino acid sites identified in other studies (4,(27)(28)(29) as having undergone strong selective pressures. Previous intersubtype studies (4, 28) examined group M subtypes independently, looking at selective pressures within each subtype.…”
Section: Discussionmentioning
confidence: 59%
“…4). Many analyses of the pattern of nucleotide substitution in the viral env gene have detected evolution in response to positive selection (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), although relatively few studies have linked these patterns of viral genetic variation to selection by defined immune responses or for changes in viral phenotype associated with coreceptor usage. In the presence of antiretroviral agents that target viral protease and reverse transcriptase, positive selection has been described in numerous studies, which demonstrate convergent evolution in different individuals of mutations that confer drug resistance (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…While it is generally assumed that selection is responsible for the appearance of recombinant forms, other possibilities, such as neutral recombination and genetic drift, have not been rigorously evaluated. Despite evidence for selection in HIV-1 env across groups of human patients (65) and evidence for selection in specific cytotoxic T lymphocyte (CTL) epitopes encoded by gag and tat in simian immunodeficiency virus (SIV)-infected macaques (1), analyses of longitudinally sampled HIV-1 sequences from individual patients have thus far failed to reveal any statistically clear examples of natural selection acting during chronic infection in association with the development of AIDS (32; D. R. Shriner, R. Shankarappa, M. A. Jensen, D. C. Nickle, J. E. Mittler, J. B. Margolick, and J. I. Mullins, submitted for publication).…”
mentioning
confidence: 99%